Digital skills and digital citizenship education: An analysis based on structural equation modeling - Olger Gutiérrez-Aguilar; Osbaldo Turpo-Gebera; Sandra Chicaña-Huanca; Kevin Mario Laura-De La Cruz; Gerber Pérez-Postigo; Rocio Diaz Zavala; Ingrid Osorio Ccoya (Journal of Technology and Science Education)
The main objective of this study is to examine the correlation between digital skills and their correlation with digital citizenship among students enrolled at a university in Peru. The research was carried out using a sample of 906 participants, encompassing individuals of various genders, with ages spanning from 17 to 54 years. The methodology of choice aligns with a non-experimental, cross-sectional, descriptive-explanatory design. The findings of this study indicate that the development of participation skills, whether in traditional face-to-face settings or in online digital platforms, significantly influences the formation of digital citizenship. The aforementioned observation holds considerable ramifications for the field of digital skills education, underscoring the imperative to prioritize and actively advocate for the development of participation skills in the context of the digital age. The importance of digital skills in our contemporary society is widely acknowledged. However, the connection between digital skills and digital citizenship is intricate and complex.